ULTRASTRUCTURE OF BLOOD CAPILLARIES IN THE MYOCARDIUM OF JUVENILE AND YOUNG RATS WITH CONGENITAL HYPOTHYROIDISM - Чухрай, С.М. (World of Medicine and Biology, 2015)
Electron-microscopically studied the blood capillaries of the myocardium of the left ventricle 7 and 45 per diem rats with GED (congenital hypothyroidism). The level of free thyroxine in plasma was determined by enzyme immunoassay when removing the rats from the experiment. It is established that in juvenile 7-diurnal and rats with congenital hypothyroidism significant changes in blood capillaries of the myocardium at the ultrastructural level was not observed, and the possible restructuring at the molecular level are yet to be fully compensated due to the adaptive capacity of a young body, which helps to counteract the effect of pathological factors, which are deficiency of thyroid hormones and to prevent the development of structural damage. Young (45 and diurnal) animals with GED in the blood capillaries of the myocardium of the left ventricle develop the complex changes that have attributes of both compensatory-adaptive and destructive-dystrophic processes. In the blood capillaries of the myocardium of rats with GED enhanced transendothelial processes of transport of substances occurs due to impaired biosynthetic processes. Destructive-dystrophic processes are manifested by lysіs and swelling of the cytoplasm and organelles in endotheliocyte. Part of the endothelial cells found at different stages of apoptosis.
Keywords: myocardium; blood capillaries; rats; congenital hypothyroidism; electron microscopy